Numeracy literacy outcomes of RME with local wisdom across cognitive styles - Izzatin, Maharani; Kartono; Zaenuri, Zaenuri; Dewi, Nuriana Rahmani (KALAMATIKA Jurnal Pendidikan Matematika, 2025)
Numeracy literacy is a crucial skill involving the use of numbers, symbols, and basic mathematical concepts in daily life. However, PISA results indicate that Indonesian students’ numeracy literacy remains low, highlighting the need for effective learning models. This study examined the integration of the Realistic Mathematics Education (RME) model with Kudus local wisdom to enhance students’ numeracy literacy, taking into account their cognitive styles. Kudus local wisdom encompasses traditions such as Dandangan and local products like parijoto fruit, jenang, batik, sarongs, and embroidered kebaya. The research involved seventh-grade students at a state junior high school in Kudus and employed a quantitative quasi-experimental design with a 2×2 factorial arrangement. The Group Embedded Figures Test (GEFT) was used to identify students’ cognitive styles, while a numeracy literacy test measured learning outcomes. Data were analyzed using two-way ANOVA. The results showed that: (1) the RME model significantly improved numeracy literacy (p = 0.011); (2) cognitive style did not have a significant effect on numeracy literacy (p = 0.615); and (3) there was no significant interaction between learning model and cognitive style (p = 0.272). In conclusion, the RME model effectively enhances numeracy literacy regardless of students’ cognitive styles. Its integration with local wisdom not only supports student competencies but also aligns with the Merdeka Curriculum’s vision of meaningful learning and contributes to achieving the Pancasila Student Profile.